LITERATURE REVIEW RESIKO KANKER LEHER DAN KEPALA PADA PENGUNAAN TEMBAKAU KUNYAH - Tuhumury, Filian; Kertadjaya, Wiwi; Purnamawati, Purnamawati (Universitas Kristen Krida Wacana, 2024)
Cancer is a disease characterized by abnormal growth of body tissue cells that then turn into cancer cells. Among the many types of cancer, head and neck cancer is one type of cancer that develops around the tissues and organs of the head and neck. Some risk factors that can increase a person's chances of developing head and neck cancer are tobacco smoking, including chewing tobacco. The use of chewed tobacco produces more than 70 carcinogens, such as tobacco specific nitrosamines (TSNA), polycyclic aromatic hydrocarbons (PAHs), aldehydes, and heavy metals. as the main cause of head and neck cancer. This literature review was made to determine the risk of neck and head cancer in the use of chewing tobacco. The method in making this review literature is in the form of a literature review by collecting several theoretical foundations from various research journals, the internet, and other scientific articles. Collect research journals from various databases for analysis. Journals or articles obtained are the results of searches on Google Scholar, ProQuest and PubMed. The results of this literature review show that there is a significant association between the risk of head cancer and the use of chewing tobacco.